Adsorption Behavior of Fatty Alcohol Ether Sulfonate at Different Interfaces. Issue 2 (6th January 2017) - Liu, Xiaochen; Zhao, Yongxiang; Li, Qiuxiao; Jiao, Tiliu; Niu, Jinping
Abstract: The equilibrium surface tension, dynamic surface tension, and interfacial tension (IFT) of fatty alcohol ether sulfonates (C m E n SO) were measured to investigate their adsorption behavior. The effect of NaCl and CaCl2 concentrations on the IFT was also studied. The results showed that the number of EO units has no significant effect on the critical micelle concentration (CMC) and CMC decreases with increasing the length of the hydrophobic group. The surface tension at the CMC increases with the increase of the number of EO units and the length of the hydrophobic group. At dilute surfactant concentration, the adsorption process for C m E n SO is controlled by diffusion; at higher concentration, it becomes a mixed diffusion‐kinetic adsorption mechanism. The IFT between C m E n SO solution and dodecane remains around 10 −1 mN/m over a wide range of electrolyte concentrations (NaCl concentration from 25 to 210 g/L, CaCl2 concentration from 0.1 to 10 g/L).